干式双离合器的发展动态 - 赵韩; 冯关华; 黄康; 陈奇 (Jixie chuandong)
Dry dual clutch is one of important components of the dual clutch transmission,and the transmission of the power and the quality of shifting of transmission are directly influenced by the performance of the dry dual clutch.In order to learn about the development trend of the dry dual clutch comprehensively,its concept and characteristics and applications are illustrated,its structure and current researches at home and broad are introduced,and the advantages and disadvantages of various structure are summarized,the technical difficulties in the process of design are pointed out,and the development trend of the dry dual clutch is proposed.The theoretical foundation for the future research and development of the dry dual clutch is provided.